(3QSGdI aj GdLeYIs - (3CMeO Hf eMeO GdeUQjs ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH GdYHO GdSdGe s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdefGd CeG HYO ajbhd aLQ GdHMK hGdSDGd Yf Mce GdUdGI GdLeYI ai gPG GdHdO s
(3BNQgG (B:s
(3hef jbd CfG TGaYi HdSGfg hde jcf eQJVjkG HLfGfg adjS dfG eYg NWGH hGddg hQShdg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs